Dihydrocodeine/Agonists for Alcohol Dependents - Ulmer, Albrecht; Müller, Markus (Frontiers in Psychiatry, 2012)
Objective: Alcohol addiction too often remains insufficiently treated. It shows the same profile as severe chronic diseases, but no comparable, effective basic treatment has been established up to now. Especially patients with repeated relapses, despite all therapeutic approaches, and patients who are not able to attain an essential abstinence to alcohol, need a basic medication. It seems necessary to acknowledge that parts of them need any agonistic substance, for years, possibly lifelong. For >14 years, we have prescribed such substances with own addictive character for these patients. Methods: We present a documented best possible practice, no designed study. Since 1997, we prescribed Dihydrocodeine (DHC) to 102 heavily alcohol addict-ed patients, later, also Buprenorphine, Clomethiazole (>6 weeks), Baclofen and in one case Amphetamine, each on individual indication. This paper focuses on the data with DH, especially. The Clomethiazole-data has been submitted to a German journal. The number of treatments with the other substances is still low. Results: The 102 patients with the DHC-treatment had 1367 medically assisted detoxifications and specialized therapies before! The 4 years-retention rate was 26.4%, including 2.8% successfully terminated treatments. In our 12-step scale on clinical impression, we noticed a significant improvement from mean 3.7 to 8.4 after 2 years. The demand for medically assisted detoxifications in the 2 years remaining patients was reduced by 65.5%. Mean GGT improved from 206.6 U/l at baseline to 66.8 U/l after 2 years. Experiences with the other substances are similar but different in details. Conclusions: Similar to the Italian studies with GHB and Baclofen, we present a new approach, not only with new substances, but also with a new setting and much more trusting attitude. We observe a huge improvement, reaching an almost optimal, stable, long term status in around ¼ of the patients already. Many further optimizations are possible.